(untitled) (European journal of volunteering and community-based projects, 2020)
BACKGROUNG: About 10% of newborns under 1000 g have problems related to candidiasis. The mortality rate is still very high today, and new types of drugs are used for the treatment. To this end, the researcher conducts a systematic review concerning the clinical use of the micafungin drug in children and its impact regarding cost-effectiveness. METHODS: The research used the PRISMA statements methodology to include all clinical and economic findings concerning the treatment of candidiasis through micafungin in infants and children. RESULTS: The research considers 13 clinical sources related to the use of micafungin belonging to the echinocandin family and a source of an economic nature. As highlighted by the research, micafungin is used in neonates for candida treatment with doses ranging from 0.4 to 10 mg/kg/ day on average for 15 days, and in children, the dose decreases slightly between 0.8 and 7.7 mg/kg/ day with a treatment period between 5 and 45 days. CONCLUSIONS: The use and efficacy of micafungin are features validated by several international clinical trials, success rates and conclusions confirm its validity. The analysis present in the literature on costs highlights how this disease is associated with higher costs due to the high number of days of hospitalization and for the administration of the drug.